SENI TARI DALAM PANDANGAN ISLAM - Tri Yuliana Wijayanti (IAIN Batusangkar, 2018)
Humans in their daily lives cannot be separated from art. Art is a form of aesthetic expression towards human existence as a servant. Expressions of beauty that are expressed through beautiful movements, will give birth to exotic dance. Speaking of dance, in general, the negative prejudices of both dancers and dances are generally generated. This is interesting to study when drawn with the flexibility of Islamic teachings and the core of Islamic teachings themselves, namely tauhid.